Identifying prioritized afforestation types in ecologically vulnerable zones of Northern China considering reducing water consumption and increasing carbon sequestration - Yanmin Teng; Jinyan Zhan; Meirong Su; Yiping Wu; Yuan Zhang; Chunxue Yu; Chao Xu (Ecological Indicators, 2022)
Afforestation is one of the most important measures to control soil erosion and desertification in Northern China. Meanwhile, considering that afforestation in Northern China needs to increase carbon sequestration (CS) and reduce water consumption (WC), it is essential to select prioritized afforestation types in suitable regions. In this work, we identified ecologically vulnerable zones based on soil water and wind erosion assessment, evaluated tree and shrub afforestation suitability, and thus recognized potential afforestation regions. Further, we set four scenarios for different goals, and identified the prioritized afforestation types in each scenario. The results showed that potential afforestation regions are mainly distributed in the Loess Plateau, Western Liao River, Ordos Plateau, and Tarim Basin. Scenario 1 (aiming to minimize WC) is dominated by shrub afforestation and grassland restoration. This scenario will reduce WC by 3.1%-6.4% compared to other scenarios, but it will also decrease CS by 9.4%-56.1% and soil conservation (SC) by 7.7%-13.0%. Scenario 2 (aiming to maximize CS) is dominated by tree and shrub afforestation. This scenario will fix 41.8%-56.1% more carbon, and consume 3.0%-6.4% more water than the other scenarios. Meanwhile, this scenario can maximize SC, but also may reduce sand fixation (SF). Scenario 3 (aiming to maximize CS in humid region and minimize WC in arid region) and Scenario 4 (aiming to enhance both SC and SF) are dominated by shrub afforestation, tree afforestation and grassland restoration. The two scenarios can balance CS and WC, and have advantages in improving both SC and SF. In addition, Scenario 4 performs better than Scenario 3. In the future, it is better to implement tree afforestation mainly in sub-humid area, and conduct shrub afforestation mainly in arid and semi-arid regions. This study can provide guidance for the planning and management of afforestation projects in Northern China and other water scarcity areas.